Application of CFD for designing conventional three phase oilfield separator - Ahmadreza Ghaffarkhah; Mohammadjavad Ameri Shahrabi; Mostafa Keshavarz Moraveji; Hooman Eslami (Egyptian Journal of Petroleum)
This paper implemented two well-known semi-empirical procedures to estimate the dimensions of the three phase horizontal vessel. We then exercised a comprehensive Computational Fluid Dynamic (CFD) simulation to investigate the three phase separation phenomenon within each vessel. The results of numerical calculation in terms of three phase fluid profiles, separation performance and secondary particles behavior were analyzed. Furthermore, the particles kinetic energy and mass distribution of the secondary phases were calculated on the different planes within the separators to evaluate the microscopic features of the phase separation process. At the design stage, numerical calculation results alone did not address an optimize outcomes. However, CFD simulation offered a powerful guidelines for comparison between different semi-empirical approaches and understanding how large to build a vessel.